2018
DOI: 10.1101/423806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicotinic and Cholinergic Modulation of Reward Prediction Error Computations in the Ventral Tegmental Area: a Minimal Circuit Model

Abstract: 2 Dopamine (DA) neurons in the ventral tegmental area (VTA) are thought to encode reward 3 prediction errors (RPE) by comparing actual and expected rewards. In recent years, much work 4has been done to identify how the brain uses and computes this signal.While several lines of 5 evidence suggest the the interplay of he DA and the inhibitory interneurons in the VTA implements 6 the RPE computaiton, it still remains unclear how the DA neurons learn key quantities, for 7 example the amplitude and the timing of pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…More effort is yet needed to further disentangle these neural mechanisms. For instance, more realistic neuron models could offer a complemen-tary insight into the learning process [Deperrois and Gutkin, 2018]. It has also been suggested that to be able to account for both learningand motivation-related processes, it is important to distinguish dopamine cell firing from local dopamine release on dopamine terminals [Berke, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…More effort is yet needed to further disentangle these neural mechanisms. For instance, more realistic neuron models could offer a complemen-tary insight into the learning process [Deperrois and Gutkin, 2018]. It has also been suggested that to be able to account for both learningand motivation-related processes, it is important to distinguish dopamine cell firing from local dopamine release on dopamine terminals [Berke, 2018].…”
Section: Discussionmentioning
confidence: 99%